Systematic expression analysis of cysteine‐rich secretory proteins, antigen 5, and pathogenesis‐related 1 protein (CAP) superfamily in Arabidopsis - Megumi Matsuzawa; Takumi Nakayama; Masa H. Sato; Tomoko Hirano (Plant Direct)
Abstract The Cysteine‐rich secretory proteins (CRISPS), Antigen 5 (Ag5), and Pathogenesis‐related 1 (PR‐1) protein (CAP) superfamily members are found in multiple eukaryotic organisms, including yeasts, animals, and plants. Although one of the plant CAP family genes, PR‐1 is known to respond to pathogen infection in plants, the functions of other CAP family genes in Arabidopsis remain largely unknown. In this study, we conducted a comprehensive analysis of the similarities, loci, and expression patterns of 22 Arabidopsis CAP genes/proteins, providing a clue to elucidate their molecular functions. According to the promoter‐β‐glucuronidase (GUS) analysis, members of the Arabidopsis CAP family were expressed in various young tissues or organs, such as root and shoot meristems, reproductive tissues, and particularly at the lateral root initiation site before the formation of the lateral root primordium, with distinct expression specificity. In particular, CAP51, CAP52, and CAP53 were specifically expressed in the cortical cells at the lateral root developing regions, suggesting that these genes may function in lateral root development. Thus, the expression patterns of Arabidopsis CAP family genes suggest that CAP family proteins may have certain function in the expressed organs or tissues in Arabidopsis plant.